Work–Life Balance and STARA‑Related Job Insecurity as Predictors of Turnover Intention in Micro Coffee Shops During Economic Turbulence - Ahmad Nizar Yogatama; Arjhel Domingo (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2026)
This study investigates the predictors of turnover intention among micro-coffee shop employees during economic turbulence, focusing on the roles of work–life balance and Smart Technology, Artificial Intelligence, Robotics, and Algorithms (STARA) awareness. Utilizing an explanatory quantitative design, data were collected from 399 frontliner coffee shops in Malang, Indonesia, and analyzed via Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results reveal that WLB significantly enhances job satisfaction and mitigates job insecurity. However, WLB has no significant direct effect on turnover intention, its impact is fully mediated by job satisfaction. Additionally, while STARA awareness strongly triggers technology-driven job insecurity, immediate job fears do not significantly affect job satisfaction or turnover intentions due to environmental normalization. Main implications suggest that operators must foster a supportive environment to leverage WLB into actual job satisfaction and invest in frontliner coffee shops upskilling. Research is limited by its cross-sectional data and localized geographic focus.